2022
DOI: 10.1021/acs.bioconjchem.2c00436
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Peptide Toxin for Selective Visualization of the Voltage-Gated Potassium Channel KV1.3

Abstract: Upregulation of the voltage-gated potassium channel K V 1.3 is implicated in a range of autoimmune and neuroinflammatory diseases, including rheumatoid arthritis, psoriasis, multiple sclerosis, and type I diabetes. Understanding the expression, localization, and trafficking of K V 1.3 in normal and disease states is key to developing targeted immunomodulatory therapies. HsTX1[R14A], an analogue of a 34-residue peptide toxin from the scorpion Heterometrus spinifer, binds K V 1.3 with high affinity (IC 50 of 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…To demonstrate the specificity and high quantum efficacy of QDs-MgTx, it was applied to HEK293 cells transfected with GFP tagged K V 1.3 construct, and showed a strong co-localisation of QDs with GFP, yielding a more stable and stronger QD signal [ 57 ]. A very recent study showed that conjugation of the scorpion Heterometrus spinifer -derived HsTX1 analogue HsTX1 [R14A] with Cy5 allowed the visualisation of GFP-K V 1.3 channels in CHO cells [ 58 ]. Cy5-HsTX1 enabled also imaging of Kv1.3 in BV-2 microglia cells of C57BL/6 mice treated with lipopolysaccharides (LPS), known to upregulate K V 1.3 subunit.…”
Section: Optical Probes Targeting Potassium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the specificity and high quantum efficacy of QDs-MgTx, it was applied to HEK293 cells transfected with GFP tagged K V 1.3 construct, and showed a strong co-localisation of QDs with GFP, yielding a more stable and stronger QD signal [ 57 ]. A very recent study showed that conjugation of the scorpion Heterometrus spinifer -derived HsTX1 analogue HsTX1 [R14A] with Cy5 allowed the visualisation of GFP-K V 1.3 channels in CHO cells [ 58 ]. Cy5-HsTX1 enabled also imaging of Kv1.3 in BV-2 microglia cells of C57BL/6 mice treated with lipopolysaccharides (LPS), known to upregulate K V 1.3 subunit.…”
Section: Optical Probes Targeting Potassium Channelsmentioning
confidence: 99%
“…The presence of fluorescence signals in the kidney, intestine and liver of C57BL/6 mice injected with Cy5-HsTX1 [R14A] implies its potential usefulness for biodistribution studies. Authors suggest that Cy5-HsTX1 [R14A] is a useful probe to determine the location and distribution of K V 1.3 channels under physiological as well as autoimmune and neuroinflammatory conditions, associated with the upregulation of K V 1.3 channels [ 58 ].…”
Section: Optical Probes Targeting Potassium Channelsmentioning
confidence: 99%
“…In many cases, the labeling strategy includes the construction of a mutated peptide (by inserting Tyr or Cys residue) with retained biological activity, followed by the iodination of Tyr with 125 I [ 36 , 37 ], and the labeling of Cys with [ 3 H]-N-ethylmaleimide [ 38 ] or with thiol-reactive fluorescent dyes [ 39 , 40 ]. Other approaches are based on the labeling of the N-terminal amino group with an organic fluorophore during solid-phase synthesis of the peptide [ 41 , 42 , 43 ] or the “blind” labeling of one of several Lys residues, which are present in the peptide, with an amino-reactive organic fluorophore [ 44 ]. In the latter case, the separation of labeled derivatives and the selection of the most active ones followed by the determination of the modified Lys residue are required.…”
Section: Introductionmentioning
confidence: 99%
“…19,28,29 Scorpion toxins targeting voltage-gated potassium ion (K V ) channels could also be linked to different fluorescent molecules, such as HsTX1[R14A], OSK1, and AgTx2, serving as pharmacological tools for studying K V channels. 30,31 In addition, a labeled toxin for imaging the rat TRPV1 ion channel could be obtained by connecting an agonist double-knot toxin (DkTx) with fluorescent molecules. 32 Together, these results indicate that peptide toxins with high activity and selectivity for specific subtypes of ion channels can serve as ideal pharmacological tools for visualizing and imaging ion channels when linked to various fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the fluorescent molecule 5-carboxytetramethylrhodamine succinimidyl ester (5-TAMRA-SE) could react with the N-terminus of α-CTx LtIA targeting α3β2 nAChR to obtain a novel fluorescent analog of LtIA . Other α-CTxs, such as MII and TxID (targeting α3β2 and α3β4 nAChRs, respectively), could also connect with different fluorescent molecules, providing pharmacological tools for exploring the functional neuroanatomy of various subtypes of nAChRs. ,, Scorpion toxins targeting voltage-gated potassium ion (K V ) channels could also be linked to different fluorescent molecules, such as HsTX1­[R14A], OSK1, and AgTx2, serving as pharmacological tools for studying K V channels. , In addition, a labeled toxin for imaging the rat TRPV1 ion channel could be obtained by connecting an agonist double-knot toxin (DkTx) with fluorescent molecules . Together, these results indicate that peptide toxins with high activity and selectivity for specific subtypes of ion channels can serve as ideal pharmacological tools for visualizing and imaging ion channels when linked to various fluorescent molecules.…”
Section: Introductionmentioning
confidence: 99%